Role of Agility in Audit, Corporate Governance, Risk and Compliance (AGRC) for Financial Performance in Listed Government-Owned Companies - Noora Ayoob, Mohammed Hassan (2024)
This study investigates the relationship between corporate governance mechanisms, risk, compliance, and the financial performance of listed government-owned companies in the UAE. The motive of the study in applying it to listed governmentowned companies in the UAE is the leading role played by these companies in the redistribution of national income, as this is considered one of the main objectives of establishing such companies. Hence, this study covering the research gap in the field examines the relationship between agility in audit, corporate governance, risk, compliance, and financial performance. Hence, the research is structured into five chapters to fulfill the research questions and objectives, encompassing a comprehensive review of existing related studies, an in-depth analysis and discussion of relevant literature pertinent to this research, and the exploration of a theoretical framework. Consequently, the hypotheses are rested on the basis of the conceptual framework. Also, the research methodology is discussed in this study to outline how this answers the research questions and verifies its hypotheses and the data, which are collected andanalyzed statistically. The study reached several results, the most important of which are: that enhancing the company's use of good corporate governance strives to increase shareholder welfare; one of the aspects that investors take into account when deciding whether to purchase shares of a firm is its financial performance, so Investors' money is safe and secure thanks to the application of good corporate governance. can use financial performance to gauge a manager's success in controlling resources for the organization. In the meanwhile, good corporate governance will help it perform better financially because economic performance demonstrates sound financial management also the specific results of this research revealed that regarding the independent variables of internal auditing, there are significant effects of internal auditing effectiveness, audit committee, audit agility and board director on the ROA indicator as one of the financial performance indicators. Also, there are significant effects of the internal auditing variables on the Tobins’Q as one of the financial performance indicators. Therefore, it is necessary to conduct more studies on the relationship between governance mechanisms and financial performance in other business sectors.